Analisis Makna Kata Enak dan Kuchi Sebagai Polisemi (Kajian Linguistik kognitif) - Sulhiyah Sulhiyah (Faculty of Economics, Law, and Humanities, 2018)
As a system, language consists of several elements or levels that form a complete construction. These elements are sounds or phonemes, morphemes, words, phrases, clauses, sentences, paragraphs, and discourses. Furthermore, these elements can be studiedthrough the branches of linguistics that have been available in accordance with theseelements. This study aims to determine the classifcation of the meaning of polysemicmeaning